Turning around Cycles: An Approach Based on Selected Problems/Cases to Stimulate Collaborative Learning about Krebs and His Four Metabolic Cycles - Medina-Torres, Miguel Ángel; García-Ponce, Ángel Luis; Blanco-López, Ángel; Rodríguez-Quesada, Ana María; Urdiales-Ruiz, José Luis; Fajardo-Paredes, Ignacio José; Suárez-Marín, María Fernanda; Alonso-Carrión, Francisco José (ACS, 2022)
Metabolism is a challenging subject for bioscience students due to the intrinsic complexity of the metabolic network, as well as that of the overlapping mechanisms of metabolic regulation. Collaborative learning based on a problem-based learning approach can help students to successfully learn and understand metabolism. In the present article, we propose a selection of exercises, problems, and cases aimed to focus students’ attention on the scientific work made by Sir Hans Krebs and his collaborators to elucidate four main metabolic cycles, as well as on the study of these cycles, their regulation, and their metabolic integration. The objectives, the tools, and the implementation of this proposal are described, and the results obtained during its first implementation with volunteer students enrolled in two courses on metabolic regulation at our university are presented and discussed. These volunteer students signed a learning contract and were randomly distributed in small groups (3–4 students each). Application of this collaborative learning activity to our classrooms has been very satisfactory, as evidenced by an improvement in the volunteers’ academic performance and a very positive perception by most of them, who declared to be “very satisfied” or “satisfied” with their experience and felt that they had learned more.
Keywords: Metabolismo; Biochemistry; Biological databases; Biology; Metabolism; Students